2013
DOI: 10.1177/2041731413508771
|View full text |Cite
|
Sign up to set email alerts
|

Porcine incisional hernia model: Evaluation of biologically derived intact extracellular matrix repairs

Abstract: We compared fascial wounds repaired with non-cross-linked intact porcine-derived acellular dermal matrix versus primary closure in a large-animal hernia model. Incisional hernias were created in Yucatan pigs and repaired after 3 weeks via open technique with suture-only primary closure or intraperitoneally placed porcine-derived acellular dermal matrix. Progressive changes in mechanical and biological properties of porcine-derived acellular dermal matrix and repair sites were assessed. Porcine-derived acellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
3
3
0
1
Order By: Relevance
“…The results of this study compare well with similar, previously published studies [ 24 , 25 , 27 , 32 ]. In 2013, Deeken et al evaluated Phasix™ in a porcine model of hernia repair at 6, 12, 26, and 52 weeks postimplantation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study compare well with similar, previously published studies [ 24 , 25 , 27 , 32 ]. In 2013, Deeken et al evaluated Phasix™ in a porcine model of hernia repair at 6, 12, 26, and 52 weeks postimplantation.…”
Section: Discussionsupporting
confidence: 92%
“…In a third study, Monteiro et al evaluated Strattice™ in a porcine model at 2, 4, and 6 weeks postimplantation. These results were also comparable to the results of Strattice™ in the current study and showed a mild inflammatory response with rapid 40, 84, and 81 % decline in mesh strength at 2, 4, and 6 weeks, respectively [ 27 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hernia abdominalis dapat diperbaiki dengan cara penjahitan atau dengan bantuan mesh bedah (Monteiro et al, 2013). Penggunaan metode jahitan sebagai terapi primer maupun sekunder sering menimbulkan kejadian berulang pada hernia abdominalis (Doctor, 2006).…”
Section: Pendahuluanunclassified
“…The enzymatic processing of Strattice significantly reduces the amount of α-Gal epitope in the absence of damage to the matrix integrity (collagen and elastin architecture). 69 Clinically, Strattice may enhance soft-tissue support in patients with poor-quality mammary soft-tissue support, especially in implant-based breast reconstruction post mastectomy and in certain patients undergoing augmentation mammoplasty. The tissue matrix is provided in two forms -pliable and firm.…”
Section: Stratticementioning
confidence: 99%